MATHEMATICAL ANALYSIS OF COVID-19 INFECTION MODEL WITH DEMOGRAPHIC DYNAMICS (FUDMA JOURNAL OF SCIENCES, 2024)
This study developed a deterministic mathematical model of COVID-19 infection by incorporating asymptomatically and symptomatically infectious individuals, the vital dynamics such as birth rate and mortality rate. Face mask use, diagnosis of asymptomatic infectious individuals, and isolation of infected individuals as control strategies are also incorporated. The model is shown to have two unique equilibrium states, namely: the disease-free equilibrium points and the endemic equilibrium point. The result from the stability analysis of the critical points is shown to be local asymptotic stable and also, globally asymptotically stable provided the basic reproduction number is less than one (, and the endemic equilibrium state is local asymptotic stable and also, globally asymptotically stable provided . Furthermore, results of the sensitivity index on   for the different parameters of the model show that the recruitment rate and the effective contact rate are the most sensitive parameters and thus critical in disease management and eradication. Thus, efforts geared at reducing the recruitment of susceptible individuals and infection transmission rate will significantly eliminate the disease burden.
Keywords: COVID-19; Positivity of Solution; Equilibrium Points; Basic Reproduction Number; Stability